Party ballots, reform, and the transformation of America's electoral system - Engstrom, Erik J.; Kernell, Samuel, 1945- (Cambridge : Cambridge University Press, 2014)
This book explores the fascinating and puzzling world of nineteenth- and early twentieth-century American elections. It examines the strategic behavior of nineteenth-century party politicians and shows how their search for electoral victory led them to invent a number of remarkable campaign practices. Why were parties dedicated to massive voter mobilization? Why did presidential nominees wage front-porch campaigns? Why did officeholders across the country tie their electoral fortunes to the popularity of presidential candidates at the top of the ticket? Erik J. Engstrom and Samuel Kernell demonstrate that the defining features of nineteenth-century electoral politics were the product of institutions in the states that prescribed how votes were cast and how those votes were converted into political offices. Relying on a century's worth of original data, this book uncovers the forces propelling the nineteenth-century electoral system, its transformation at the end of the nineteenth century, and the implications of that transformation for modern American politics.
1. An era in need of explanation -- 2. The puzzle of responsive elections -- 3. National forces in presidential elections -- 4. House of Representatives elections -- 5. Senate indirect and direct elections -- 6. State legislative elections -- 7. Gubernatorial elections -- 8. Dismantling the party-ticket system -- Appendix: states as bundles of electoral laws, 1840-1940.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Elections -- United States -- History -- 19th century; Political campaigns -- United States -- History -- 19th century; Voting -- United States -- History -- 19th century; Political parties -- United States -- History -- 19th century; United States -- Politics and government -- 19th century